High-adhesion high-support high-temperature and low-temperature creep resistant 3D fiber mesh hollow structure and preparation method thereof

CN117926455BActive Publication Date: 2026-10-09ORINKO HIGH PERFORMANCE MATERIALS TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311804183.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2026-10-09
Estimated Expiration
2043-12-26

AI Technical Summary

Technical Problem

[0004]基于此,针对目前3D纤维垫芯材料在使用过程中长期受压容易出现蠕变(特别是高温蠕变)、回弹性和支撑力变差、舒适性体验大打折扣等问题,本发明的目的提供一种高粘接高支撑抗高低温蠕变3D纤维网状中空结构体及其制备方法,通过引入低熔点接枝聚合物以及具有高导热性能的零维碳材料、范德华异质体、针或棒状材料,能够在结构体中形成桥状骨架或网络的高效导热通路,当有微量热流经过导热通路时,会传导热量使聚醚酯热塑性弹性体温度升高,使3D纤维网状中空结构体具有良好的热致形状记忆恢复特性以及良好的高粘接点、高支撑性与长期抗高低温蠕变特性,进而实现形状快速恢复

Benefits of technology

[0026]1. The high-adhesion, high-support, and high- and low-temperature creep-resistant 3D fiber mesh hollow structure of the present invention incorporates zero-dimensional carbon materials, van der Waals heterostructures, and needle- or rod-shaped materials with high thermal conductivity. These materials form highly efficient thermally conductive pathways, creating a bridge-like skeleton or network within the structure. When a small amount of heat flows through these pathways, it conducts heat, raising the temperature of the polyether ester thermoplastic elastomer. This results in the 3D fiber mesh hollow structure exhibiting excellent thermoinduced shape memory recovery characteristics, as well as good high adhesion points, high support, and long-term resistance to high and low temperature creep, thereby achieving rapid shape recovery. The 3D fiber mesh hollow structure of the present invention can be used in ergonomic, long-term pressure-resistant, electrically heated seat cushion cores and mattress cores. Simultaneously, the introduction of low-melting-point grafted polymers in this invention improves the flowability and underwater bonding density of the polyether ester thermoplastic elastomer, indirectly reducing the compression set of the finished 3D air fiber hollow structure and improving its support and comfort. This invention utilizes the combined effects of low-melting-point grafted polymers, zero-dimensional carbon materials, needle- or rod-shaped materials, and van der Waals heterostructures to obtain a relatively ideal spun fiber structure with high adhesion, creep resistance, and a certain shape memory and resilience response. In particular, the high-hardness resin preparation retains the original good support effect while possessing good resilience and comfort.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004629764610000161
    Figure BDA0004629764610000161
  • Figure BDA0004629764610000171
    Figure BDA0004629764610000171
  • Figure BDA0004629764610000172
    Figure BDA0004629764610000172
Patent Text Reader

Abstract

The present application relates to a kind of high bonding high support high and low temperature creep resistance 3D fiber mesh hollow structure and its preparation method, the high bonding high support high and low temperature creep resistance 3D fiber mesh hollow structure is prepared from the following weight parts of component:35-90 parts benzoate and its derivative, 10-65 parts polyether alcohol, 0.05-0.2 parts catalyst, 2-20 parts low melting point graft polymer, 0-2 parts zero-dimensional carbon material, 0.2-2 parts needle or rod material, 0.2-2 parts van der waals heterostructure, 0.2-2 parts processing aid.The present application can obtain ideal high bonding creep resistance and have certain shape memory resilience response spinning fiber structure by the low melting point graft polymer, zero-dimensional carbon material, needle or rod material, van der waals heterostructure mutual effect, especially high hardness resin is prepared in the case where original good supporting effect is retained, has good resilience and comfort.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and in particular to a high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber mesh hollow structure and its preparation method. Background Technology

[0002] Polyether ester thermoplastic elastomer (TPEE) is a type of copolymer polymer material that combines the elasticity of thermosetting rubber with the processability of thermoplastics; it is also known as polyether ester synthetic rubber. It possesses excellent resistance to high and low temperatures, weathering, and chemicals, and is moldable using common thermoplastic processing equipment. Furthermore, it is reusable, and the performance of products obtained through recycling and reprocessing is not significantly diminished. It is replacing some thermosetting vulcanized rubber materials and is widely used in the automotive industry and consumer applications.

[0003] Polyether ester thermoplastic elastomers can be processed into long, thick fibers for use in various 3D hollow structural components such as seat cushion cores, mattress cores, and backrest cushion cores. They offer unparalleled support, breathability, and user comfort compared to foamed polyurethane, latex products, and spring / sponge composites. However, in high-altitude and cold regions, polymer materials subjected to prolonged weight and pressure can undergo significant deformation and plastic creep, failing to recover quickly over extended periods. This is particularly true for high-hardness support materials like seat cushion cores, severely impacting seating comfort and potentially causing long-term spinal health problems. Summary of the Invention

[0004] Based on this, and addressing the problems of creep (especially high-temperature creep), decreased resilience and support, and significantly reduced comfort that often occur with current 3D fiber core materials under long-term pressure during use, the present invention aims to provide a highly adhesive, highly supportive, and creep-resistant 3D fiber mesh hollow structure and its preparation method. By introducing low-melting-point grafted polymers and zero-dimensional carbon materials, van der Waals heterostructures, needle-like or rod-like materials with high thermal conductivity, a highly efficient thermally conductive pathway can be formed in the structure, creating a bridge-like skeleton or network. When a small amount of heat flows through the thermally conductive pathway, it conducts heat, raising the temperature of the polyether ester thermoplastic elastomer. This gives the 3D fiber mesh hollow structure excellent thermo-induced shape memory recovery characteristics, as well as good high adhesion points, high support, and long-term creep resistance to high and low temperatures, thereby achieving rapid shape recovery.

[0005] To achieve the above objectives, the present invention adopts the following technical solution:

[0006] This invention provides a high-adhesion, high-support, and high- and low-temperature creep-resistant 3D fiber mesh hollow structure, which is prepared from the following components in parts by weight: 35-90 parts benzoate and its derivatives, 10-65 parts polyether alcohol, 0.05-0.2 parts catalyst, 2-20 parts low-melting-point grafted polymer, 0-2 parts zero-dimensional carbon material, 0.2-2 parts needle or rod material, 0.2-2 parts van der Waals heterostructure, and 0.2-2 parts processing aid.

[0007] As a further improvement to the above-mentioned scheme of the present invention, the zero-dimensional carbon material is at least one of the following: carboxyl / amino modified carbon quantum dots (including carbon nanotube quantum dots), carbon quantum dots modified polyethylene glycol adamantane, carboxyl water-soluble ZnCdSe / ZnS quantum dots (PEG (carboxyl or amino) as ligand), carbon quantum dot copper, (rare earth doped) perovskite quantum dots, cyclodextrin modified calcium phosphate nanoparticles / zinc sulfide quantum dots, cadmium selenide quantum dots, indium phosphide quantum dots, graphene quantum dots, graphitic carbon nitride quantum dots, PEG functionalized graphene quantum dots loaded with cisplatin (PEG-GQDs-Pt, GPt), gold nanoparticles, and silver nanoparticles. These materials are mainly spherical structures, with strong stability, low surface energy, and are not easily bonded between particles, thus exhibiting good thixotropy, good heat retention function, high specific surface area, and easy dispersibility.

[0008] As a further improvement of the above-mentioned solution of the present invention, the needle or rod-shaped material is at least one of titanium dioxide nanofibers, carboxyl carbon nanotubes, carbon nanofibers, and transition metal dichalcogenide nanotubes; the needle or rod-shaped material has good dispersibility and thermal conductivity, as well as the characteristic of building a heat transfer and heat conduction network structure.

[0009] And / or, the aspect ratio of the needle or rod material is 1.5:1 to 5:1.

[0010] As a further improvement to the above-described scheme of the present invention, the van der Waals heterostructure is a graphene / graphene stacked van der Waals heterostructure, a graphene / molybdenum disulfide van der Waals heterostructure, a graphene / gallium phosphide van der Waals heterostructure, a graphene / boron boron nitride van der Waals heterostructure, a graphene / hexagonal boron nitride / molybdenum disulfide van der Waals heterostructure, a molybdenum disulfide / antimony trisulfide van der Waals heterostructure, a black phosphorus / molybdenum disulfide van der Waals heterostructure, a graphene / trinitrobenzene van der Waals heterostructure, a graphene / titanium dioxide van der Waals heterostructure, a graphene / transition metal dihalide MX2 van der Waals heterostructure, or a molybdenum disulfide / titanium trisulfide van der Waals heterostructure. The above-mentioned van der Waals heterostructures include at least one of the following: graphene / nano-silica van der Waals heterostructure, black phosphorus / germanium phosphide van der Waals heterostructure, molybdenum disulfide / gallium phosphide van der Waals heterostructure, graphene / copper selenide van der Waals heterostructure, graphene / gallium nitride van der Waals heterostructure, black phosphorus / antimony trisulfide van der Waals heterostructure, indium tin oxide / aluminum oxide van der Waals heterostructure, and graphene / silica nanowire van der Waals heterostructure. In the above-mentioned van der Waals heterostructures, each layer retains its inherent properties and can interact with adjacent layers through weak interlayer interactions. This electronic structure endows the van der Waals heterostructures with the properties of efficiently conducting charge carriers, charges, and thermally conductive heat transfer carriers.

[0011] As a further improvement to the above-described scheme of the present invention, the benzoic acid ester and its derivatives are at least one of dimethyl phthalate, dimethyl isophthalate, ethylene isophthalate, ethylene phthalate, propylene isophthalate, propylene glycol phthalate, butylene isophthalate, butylene phthalate, diphenyl phthalate, a copolymer of dimethyl 1,4-phthalate with 1,4-cyclohexanediol and 1,2-ethylene glycol, 1,4-dimethylenecyclohexane terephthalate, and butylene 2,6-naphthalenedicarboxylate.

[0012] As a further improvement to the above-mentioned scheme of the present invention, the polyether alcohol is at least one of polyoxypropylene polyol, diethylene glycol diethyl ether, polyoxytetramethylene polyol, and tetrahydrofuran-propylene oxide copolydiol.

[0013] As a further improvement to the above-described scheme of the present invention, the low-melting-point graft polymer is an AgB-type graft polymer or a high melt index, low-melting-point hot-melt polyurethane. The low-melting-point graft polymer should have low (slow) heat dissipation or heat retention characteristics and excellent bond strength. Preferably, the grafting rate of the AgB-type grafted polymer is at least 0.8%, and the melting point is 90-140°C. Component A is a copolymer of low-melting-point, low-glass transition-temperature POE, EPDM, PP, EVA, or SEBS with a molecular weight between 3000 and 7000. Component B is GMA, MAH, or epoxy functional groups. Preferably, the melt index of the high melt index, low-melting-point hot-melt polyurethane is at least 10 g / 10 min (190°C, 2.16 kg), and it is selected from at least one of WHT-6290, WHT-6227C, WHT-6275H, WHT-6236, WHT-6228C, WHT-6235B, WHT-6229C, WHT-6420C, WHT-6229, and WHT-6232.

[0014] As a further improvement to the above-described scheme of the present invention, the catalyst is one of zirconium oxide, zirconium hydroxide, and ruthenium / zirconium chelate;

[0015] And / or, the processing aid is at least one of the following: long-chain linear saturated lignite, sodium dodecyl sulfate, sodium allyl sulfonate, potassium dodecylbenzene sulfonate, calcium stearate, aluminum stearate, calcium distearate, aluminum distearate, aluminum dihydroxystearate, glyceryl monostearate, stearyl citrate, and quaternary ammonium salt.

[0016] This invention also proposes a method for preparing a high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber mesh hollow structure as described above, comprising the following steps:

[0017] S1. Benzoate and its derivatives, catalyst and low-melting-point graft polymer are added to a nitrogen-filled polymerization reactor in proportion, and 40-80% of the total polyether alcohol is added. The reaction is carried out at 160-240℃ for 40-120 min to obtain transesterification and grafting products.

[0018] S2. Hydroxyl and / or carboxyl groups are used to modify zero-dimensional carbon materials, needle-shaped or rod-shaped materials, and van der Waals heterostructures to obtain zero-dimensional carbon materials, needle-shaped or rod-shaped materials, and van der Waals heterostructures modified with hydroxyl and / or carboxyl groups.

[0019] S3. Under constant temperature conditions of 60-100℃, the zero-dimensional carbon material modified with hydroxyl and / or carboxyl groups is added to the remaining polyether alcohol in proportion and ultrasonically stirred. Then, the needle or rod-shaped material modified with hydroxyl and / or carboxyl groups is added in proportion and ultrasonically stirred again. Finally, the van der Waals heterostructure modified with hydroxyl and / or carboxyl groups is added in proportion and ultrasonically stirred again to obtain a homogeneous polyether alcohol mixture.

[0020] S4. Add the polyether alcohol mixture to the polymerization reactor, and add processing aids in proportion, and carry out a secondary reaction with the transesterification and grafting product for 0.5 to 2 hours.

[0021] S5. Remove nitrogen from the polymerization reactor to a vacuum negative pressure of 0.02-0.4 MPa, and simultaneously raise the temperature to 190-230°C to carry out a vacuum low-viscosity final polycondensation reaction for 1-2 hours. Discharge and granulate to obtain thermoplastic polyether ester elastomer. Extrude and spin the thermoplastic polyether ester elastomer to obtain a high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber network hollow structure.

[0022] As a further improvement to the above-described scheme of the present invention, in step S2, the process of hydroxyl and / or carboxyl modification is as follows: the zero-dimensional carbon material, needle or rod-shaped material, and van der Waals heterostructure are respectively immersed in an acid solution and oxidized at a constant temperature of 80-120°C for 8 hours; then washed and dried to obtain zero-dimensional carbon material, needle or rod-shaped material, and van der Waals heterostructure modified with hydroxyl and / or carboxyl groups; preferably, the acid solution is a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1.

[0023] And / or, in step S4, when the amount of alcohol in the transesterification and grafting product reaches more than 120% of the amount of benzoate and its derivatives, the polyether alcohol mixture is added.

[0024] And / or, in step S5, when the viscosity of the mixture in the polymerization reactor reaches 4000-6000 Pa·s, the nitrogen in the polymerization reactor is then purged to a vacuum negative pressure of 0.02-0.4 MPa.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The high-adhesion, high-support, and high- and low-temperature creep-resistant 3D fiber mesh hollow structure of the present invention incorporates zero-dimensional carbon materials, van der Waals heterostructures, and needle- or rod-shaped materials with high thermal conductivity. These materials form highly efficient thermally conductive pathways, creating a bridge-like skeleton or network within the structure. When a small amount of heat flows through these pathways, it conducts heat, raising the temperature of the polyether ester thermoplastic elastomer. This results in the 3D fiber mesh hollow structure exhibiting excellent thermoinduced shape memory recovery characteristics, as well as good high adhesion points, high support, and long-term resistance to high and low temperature creep, thereby achieving rapid shape recovery. The 3D fiber mesh hollow structure of the present invention can be used in ergonomic, long-term pressure-resistant, electrically heated seat cushion cores and mattress cores. Simultaneously, the introduction of low-melting-point grafted polymers in this invention improves the flowability and underwater bonding density of the polyether ester thermoplastic elastomer, indirectly reducing the compression set of the finished 3D air fiber hollow structure and improving its support and comfort. This invention utilizes the combined effects of low-melting-point grafted polymers, zero-dimensional carbon materials, needle- or rod-shaped materials, and van der Waals heterostructures to obtain a relatively ideal spun fiber structure with high adhesion, creep resistance, and a certain shape memory and resilience response. In particular, the high-hardness resin preparation retains the original good support effect while possessing good resilience and comfort.

[0027] 2. This invention introduces zero-dimensional carbon materials, van der Waals heterostructures, and needle- or rod-shaped materials with high thermal conductivity into the molecular chain segments of polyether ester thermoplastic elastomers through transesterification and grafting reactions, forming a highly efficient thermally conductive pathway with a bridge-like skeleton or network. Compared with the blending process that involves filling a large amount of thermally conductive fillers, the resulting 3D fiber network hollow structure has good thermally induced shape memory recovery characteristics, as well as good high support and long-term resistance to high and low temperature creep, thereby achieving a rapid shape recovery process.

[0028] 3. The low-melting-point polyether ester thermoplastic elastomer composition prepared by this invention has high flowability in extrusion processing, meeting the requirements of non-clogging extrusion through dies with a diameter of 0.3 mm (inclusive) or above, and underwater bending, rolling, and welding of extruded strips. It can be processed into 3D fiber mesh hollow structures. The obtained 3D fiber mesh hollow structures have good resilience and comfort, good load-bearing support, and comfortable sitting or lying down. They do not have the defects of poor ventilation, stuffiness, and creep-induced collapse caused by long-term use of polyurethane foam. They can maintain the low deformation and shape of the 3D fiber mesh hollow structure after long-term repeated compression. They can be used for ergonomic seat cushion cores, mattress cores, backrest cushion cores, etc., and are suitable for heated chairs, sofas, beds and other household / public appliances, as well as heated seats and backrests in automobiles, high-speed trains, airplanes, ships and other transportation vehicles, and cold-proof and warm-insulating cushioning pads for nursery floors, etc. Detailed Implementation

[0029] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0031] The specific information of the raw materials used in the following examples and comparative examples is as follows:

[0032] 1. Benzoate esters and their derivatives

[0033] Dimethyl isophthalate, CAS number 1459-93-4, was purchased from Merck Reagents.

[0034] The CAS number for butylene phthalate is 84-74-2, and it was purchased from Shanghai Jiadeer Chemical Technology Co., Ltd.

[0035] Diphenyl phthalate has the CAS number 84-62-8 and is manufactured by Hubei Nuona Technology Co., Ltd.

[0036] The CAS number for 2,6-butylene naphthalate is 94686-82-5, and the manufacturer is Zhengzhou Alpha Chemical Co., Ltd.

[0037] 2. Polyether alcohol

[0038] The CAS number for the polyoxyethylene polyol is 25322-68-3, and the manufacturer is Dow Chemical Company of the United States.

[0039] The CAS number for diethylene glycol diethyl ether is 112-36-7, and the manufacturer is Shanghai Chuangsai Technology Co., Ltd.

[0040] The CAS number for polytetrahydrofuran ether diol is 25190-06-1, and the manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd.

[0041] 3. Catalyst

[0042] Zirconium tetroxide and zirconium hydroxide have CAS numbers 64417-98-7 and 5593-70-4, respectively, and are both manufactured by Merck Reagents.

[0043] The commercial brand name of organotitanium zirconium chelate is NPZ is manufactured by DuPont, Inc.

[0044] 4. Low-melting-point grafted polymers:

[0045] MLDPE-g-MAH, LLDPE-g-MAH and EVA-g-MAH are graded KT-12A, KT-12B and KT-26 respectively, and are all manufactured by Shenyang Ketong Plastics Co., Ltd.

[0046] The commercial grade of high melt index, low melting point hot melt TPU is WHT-6236, and the manufacturer is Wanhua Chemical Group Co., Ltd.

[0047] The EMA-g-GMA grade is EPA-810, purchased from Hangzhou Haiyi Polymer Materials Co., Ltd.

[0048] 5. Zero-dimensional carbon materials

[0049] The commercial grades of carboxyl carbon quantum dots, graphene quantum dots, carboxyl water-soluble ZnCdSe / ZnS quantum dots, and inorganic perovskite quantum dots CsPbX3 are BK101819-01, BK101837-01, BK-WA-21745-50, and BKMK1507-01, respectively, and all are manufactured by Beijing Beike New Materials Technology Co., Ltd.

[0050] 6. Needle or rod-shaped materials

[0051] The commercial grade of titanium dioxide nanofibers is DY000184, and the manufacturer is Hangzhou Heshi New Material Technology Co., Ltd.

[0052] The commercial brand name of the carboxylated carbon nanotubes is TNIMH6, and the manufacturer is Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences.

[0053] The commercial brand name of the carbon nanofiber is VGCF-H, and the manufacturer is Showa Denko Co., Ltd. of Japan.

[0054] The commercial grade of the transition metal tungsten disulfide nanotubes is 253252, and the manufacturer is Xi'an Qiyue Biotechnology Co., Ltd.

[0055] 7. Van der Waals heterostructure

[0056] The commercial grades of molybdenum disulfide (MoS2) / titanium trisulfide (TiS3) van der Waals heterostructures, graphene / selenodisulfide (SnS2) van der Waals heterostructures, graphene / platinum diselenide (PtSe2) van der Waals heterostructures, and graphene / molybdenum diselenide (MoSe2) van der Waals heterostructures are BK2021121044, BKTMDC123117-03, BKTMDC123120-03, and BKTMDC123122-03, respectively. All of them are manufactured by Beijing Beike New Materials Technology Co., Ltd.

[0057] 8. Processing aids

[0058] The commercial brand name for long-chain linear saturated lignite sodium is LICOMONT NAV 101, and the manufacturer is Clariant in Germany.

[0059] Potassium dodecylbenzenesulfonate has the CAS number 27177-77-1 and is manufactured by Shandong Lifan Chemical Co., Ltd.

[0060] The commercial grade of aluminum distearate is A303373, and the manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd.

[0061] The commercial grade of monostearate citrate is XH52802WPG7E, and the manufacturer is Jinan Shenghe Chemical Co., Ltd.

[0062] The aforementioned raw materials are commercially available.

[0063] Example 1

[0064] This embodiment proposes a highly adhesive, highly supportive, and high- and low-temperature creep-resistant 3D fiber mesh hollow structure, the preparation method of which includes the following steps:

[0065] S1. Place 35 parts of dimethyl isophthalate, 45 parts of polyethylene oxide polyol, 0.1 parts of zirconium tetroxide and 3 parts of MLDPE-g-MAH in a nitrogen-filled polymerization reactor and react at 160°C for 110 min to obtain transesterification and grafting products.

[0066] S2. The dried graphene / molybdenum disulfide van der Waals heterostructure without hydroxyl or carboxyl groups is immersed in an acid solution (a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1), and oxidized at 120°C for 8 hours. After cleaning with ethanol and drying, the graphene / molybdenum disulfide van der Waals heterostructure modified with hydroxyl and carboxyl groups can be obtained.

[0067] S3. Add 2 parts of carboxylated carbon quantum dots to 20 parts of polyethylene oxide polyol solvent and sonicate at 60°C with constant temperature and constant speed stirring for 1 hour; then add 0.5 parts of carboxylated carbon nanotubes and sonicate at 60°C with constant temperature and constant speed stirring for 2 hours; finally add 0.2 parts of hydroxyl and carboxyl modified graphene / molybdenum disulfide van der Waals heterostructure and sonicate at 60°C with constant temperature and constant speed stirring for 2 hours to obtain a homogeneous polyethylene oxide polyol mixture.

[0068] S4. When the amount of alcohol in the transesterification and grafting product obtained in step S1 reaches more than 120% of the amount of dimethyl isophthalate, add the polyethylene oxide polyol mixture obtained in step S3 to the polymerization reactor in step S1, and add 1 part of long-chain linear saturated lignite sodium to carry out a secondary reaction, which lasts for 0.5 h.

[0069] S5. When the viscosity of the mixture in the polymerization reactor in step S4 reaches 5000 Pa·s, the nitrogen gas in the polymerization reactor is removed to a vacuum negative pressure of 0.03 MPa. At the same time, the temperature is raised to 200℃ to carry out a vacuum low viscosity final polycondensation reaction. The reaction lasts for 2 hours. The material is discharged, granulated and cooled to obtain thermoplastic polyether ester elastomer. The thermoplastic polyether ester elastomer is extruded and spun to obtain a high-adhesion, high-support, high- and low-temperature creep resistant 3D fiber network hollow structure.

[0070] Example 2

[0071] This embodiment proposes a highly adhesive, highly supportive, and high- and low-temperature creep-resistant 3D fiber mesh hollow structure, the preparation method of which includes the following steps:

[0072] S1. Place 90 parts of butylene phthalate, 5 parts of diethylene glycol diethyl ether, 0.2 parts of zirconium hydroxide and 20 parts of LLDPE-g-MAH in a nitrogen-filled polymerization reactor and react at 240°C for 40 min to obtain transesterification and grafting products.

[0073] S2. The dried perovskite quantum dots, carbon nanofibers, and molybdenum disulfide (MoS2) / titanium trisulfide (TiS3) van der Waals heterostructures without hydroxyl or carboxyl groups were each immersed in an acid solution (a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1) and oxidized at constant temperatures of 80℃, 100℃, and 120℃ for 8 hours, respectively. After being cleaned with ethanol and dried, hydroxyl and carboxyl modified perovskite quantum dots, carbon nanofibers, and molybdenum disulfide (MoS2) / titanium trisulfide (TiS3) van der Waals heterostructures were obtained.

[0074] S3. Add 0.2 parts of hydroxyl and carboxyl-modified perovskite quantum dots CsPbX3 to 5 parts of diethylene glycol diethyl ether solvent and sonicate at 60°C with constant temperature and speed stirring for 1 h; then add 0.5 parts of hydroxyl and carboxyl-modified carbon nanofibers and sonicate at 60°C with constant temperature and speed stirring for 2 h; finally add 0.5 parts of hydroxyl and carboxyl-modified molybdenum disulfide (MoS2) / titanium trisulfide (TiS3) van der Waals heterostructure and sonicate at 60°C with constant temperature and speed stirring for 2 h to obtain a homogeneous diethylene glycol diethyl ether mixture;

[0075] S4. When the amount of alcohol in the transesterification and grafting product obtained in step S1 reaches more than 120% of the amount of butylene phthalate, add the diethylene glycol diethyl ether mixture obtained in step S3 to the polymerization reactor in step S1, and add 2 parts of potassium dodecylbenzenesulfonate at the same time to carry out a second reaction. The reaction lasts for 0.5 hours.

[0076] S5. When the viscosity of the mixture in the polymerization reactor in step S4 reaches 4000 Pa·s, the nitrogen gas in the polymerization reactor is removed to a vacuum negative pressure of 0.2 MPa. At the same time, the temperature is raised to 230℃ to carry out a vacuum low viscosity final polycondensation reaction. The reaction lasts for 1 hour. The material is discharged, granulated and cooled to obtain thermoplastic polyether ester elastomer. The thermoplastic polyether ester elastomer is extruded and spun to obtain a high-adhesion, high-support, high- and low-temperature creep resistant 3D fiber network hollow structure.

[0077] Example 3

[0078] This embodiment proposes a highly adhesive, highly supportive, and high- and low-temperature creep-resistant 3D fiber mesh hollow structure, the preparation method of which includes the following steps:

[0079] S1. 70 parts of diphenyl phthalate, 15 parts of diethylene glycol diethyl ether, 0.2 parts of zirconium tetroxide and 10 parts of EVA-g-MAH / high melt index low melting point grafted polymer TPU (the weight ratio between EVA-g-MAH and high melt index low melting point grafted polymer TPU is 1:1) were placed in a nitrogen-filled polymerization reactor and reacted at 160℃ for 50 min to obtain transesterification and grafting products.

[0080] S2. The dried titanium dioxide nanofibers and graphene / selenium disulfide (SnS2) van der Waals heterostructures without hydroxyl or carboxyl groups were respectively immersed in acid solutions (concentrated sulfuric acid and concentrated nitric acid were mixed at a volume ratio of 1:1) and oxidized at 100℃ and 120℃ for 8 hours respectively. After being cleaned with ethanol and dried, titanium dioxide nanofibers and graphene / selenium disulfide (SnS2) van der Waals heterostructures modified with hydroxyl and carboxyl groups were obtained respectively.

[0081] S3. Add 0.2 parts of carboxyl-modified water-soluble ZnCdSe / ZnS quantum dots to 15 parts of diethylene glycol diethyl ether solvent and sonicate at 60°C with constant temperature and speed stirring for 1 hour; then add 2 parts of hydroxyl and carboxyl-modified titanium dioxide nanofibers and sonicate at 60°C with constant temperature and speed stirring for 2 hours; finally add 1 part of hydroxyl and carboxyl-modified graphene / selenium disulfide (SnS2) van der Waals heterostructure and sonicate at 60°C with constant temperature and speed stirring for 2 hours to obtain a homogeneous diethylene glycol diethyl ether mixture;

[0082] S4. When the amount of alcohol in the transesterification and grafting product obtained in step S1 reaches more than 120% of the amount of diphenyl phthalate, add the diethylene glycol diethyl ether mixture obtained in step S3 to the polymerization reactor in step S1, and add 0.2 parts of aluminum distearate at the same time to carry out a second reaction for 0.5 hours.

[0083] S5. When the viscosity of the mixture in the polymerization reactor in step S4 reaches 6000 Pa·s, the nitrogen gas in the reactor is removed to a vacuum negative pressure of 0.1 MPa. At the same time, the temperature is raised to 240℃ to carry out a vacuum low viscosity final polycondensation reaction for 1.5 hours. The material is discharged, granulated, and cooled to obtain thermoplastic polyether ester elastomer. The thermoplastic polyether ester elastomer can be extruded and spun to obtain a high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber network hollow structure.

[0084] Example 4

[0085] This embodiment proposes a highly adhesive, highly supportive, and high- and low-temperature creep-resistant 3D fiber mesh hollow structure, the preparation method of which includes the following steps:

[0086] S1. Place 60 parts of butylene 2,6-naphthalenedioate, 20 parts of polytetrahydrofuran ether diol, 0.05 parts of organotitanium zirconium chelate and 3 parts of EMA-g-GMA in a nitrogen-filled polymerization reactor and react at 210°C for 120 min to obtain transesterification and grafting products.

[0087] S2. The dried graphene quantum dots, transition metal disulfide nanotubes, and graphene / platinum diselenide (PtSe2) van der Waals heterostructures without hydroxyl or carboxyl groups were each immersed in an acid solution (a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1) and oxidized at constant temperatures of 80℃, 100℃, and 120℃ for 8 hours, respectively. After cleaning with ethanol and drying, hydroxyl and carboxyl modified graphene quantum dots, transition metal disulfide nanotubes, and graphene / platinum diselenide (PtSe2) van der Waals heterostructures were obtained.

[0088] S3. Add 0.5 parts of hydroxyl and carboxyl-modified graphene quantum dots to 20 parts of polytetrahydrofuran ether glycol solvent and sonicate at 60°C with constant temperature and stirring for 2 hours; then add 0.5 parts of hydroxyl and carboxyl-modified transition metal disulfide nanotubes and sonicate at 60°C with constant temperature and stirring for 2 hours; finally add 1 part of hydroxyl and carboxyl-modified graphene / platinum diselenide (PtSe2) van der Waals heterostructure and sonicate at 60°C with constant temperature and stirring for 2 hours to obtain a homogeneous polytetrahydrofuran ether glycol mixture.

[0089] S4. When the amount of alcohol in the transesterification and grafting product obtained in step S1 reaches more than 120% of the amount of butylene 2,6-naphthalenedioate, add the polytetrahydrofuran ether diol mixture obtained in step S3 to the polymerization reactor in step S1, and add 0.5 parts of citrate monostearate at the same time to carry out a secondary reaction, which lasts for 0.5 hours.

[0090] S5. When the viscosity of the mixture in the polymerization reactor in step S4 reaches 5000 Pa·s, the nitrogen gas in the polymerization reactor is removed to a vacuum negative pressure of 0.4 MPa. At the same time, the temperature is raised to 200℃ to carry out a vacuum low viscosity final polycondensation reaction for 1 hour. The material is discharged, granulated and cooled to obtain thermoplastic polyether ester elastomer. The thermoplastic polyether ester elastomer can be extruded and spun to obtain a high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber network hollow structure.

[0091] Comparative Example 1

[0092] Comparative Example 1 provides a 3D fiber mesh hollow structure, the preparation method of which includes the following steps:

[0093] S1. Place 35 parts of dimethyl isophthalate, 45 parts of polyethylene oxide polyol, and 0.1 parts of zirconium tetroxide in a nitrogen-filled polymerization reactor and react at 160°C for 110 min to obtain transesterification and grafting products.

[0094] S2. When the amount of alcohol in the transesterification and grafting product obtained in step S1 reaches more than 120% of the amount of dimethyl isophthalate, 20 parts of polyethylene oxide polyol are added to the polymerization reactor in step S1, and 1 part of long-chain linear saturated lignite is added at the same time to carry out a secondary reaction, which lasts for 0.5 hours.

[0095] S3. When the viscosity of the mixture in the polymerization reactor in step S2 reaches 5000 Pa·s, the nitrogen gas in the polymerization reactor is removed to a vacuum negative pressure of 0.03 MPa. At the same time, the temperature is raised to 200℃ to carry out a low-viscosity final polycondensation reaction in a vacuum. The reaction lasts for 2 hours. The material is discharged, granulated, and cooled to obtain thermoplastic polyether ester elastomer. The thermoplastic polyether ester elastomer is extruded and spun to obtain a 3D fiber network hollow structure.

[0096] Comparative Example 2

[0097] This comparative example provides a 3D fiber mesh hollow structure, the preparation method of which includes the following steps:

[0098] S1. Place 90 parts of butylene phthalate, 5 parts of diethylene glycol diethyl ether and 0.2 parts of zirconium hydroxide in a nitrogen-filled polymerization reactor and react at 240°C for 40 min to obtain transesterification and grafting products.

[0099] S2. The dried perovskite quantum dots, carbon nanofibers, and molybdenum disulfide (MoS2) / titanium trisulfide (TiS3) van der Waals heterostructures without hydroxyl or carboxyl groups were each immersed in an acid solution (a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1) and oxidized at constant temperatures of 80℃, 100℃, and 120℃ for 8 hours, respectively. After being cleaned with ethanol and dried, hydroxyl and carboxyl modified perovskite quantum dots, carbon nanofibers, and molybdenum disulfide (MoS2) / titanium trisulfide (TiS3) van der Waals heterostructures were obtained.

[0100] S3. Add 0.2 parts of hydroxyl and carboxyl-modified perovskite quantum dots to 5 parts of diethylene glycol diethyl ether solvent and sonicate at 60℃ with constant stirring for 1 h; then add 0.5 parts of hydroxyl and carboxyl-modified carbon nanofibers and sonicate at 60℃ with constant stirring for 2 h; finally add 0.5 parts of hydroxyl and carboxyl-modified molybdenum disulfide (MoS2) / titanium trisulfide (TiS3) van der Waals heterostructure and sonicate at 60℃ with constant stirring for 2 h to obtain a homogeneous diethylene glycol diethyl ether mixture;

[0101] S4. When the amount of alcohol in the transesterification and grafting product obtained in step S1 reaches more than 120% of the amount of butylene phthalate, add 15 parts of diethylene glycol diethyl ether to the polymerization reactor in step S1, and add 2 parts of potassium dodecylbenzenesulfonate at the same time to carry out a secondary reaction, which lasts for 0.5 hours.

[0102] S5. When the viscosity of the mixture in the polymerization reactor in step S2 reaches 4000 Pa·s, the nitrogen gas in the polymerization reactor is removed to a vacuum negative pressure of 0.2 MPa. At the same time, the temperature is raised to 230℃ to carry out a vacuum low viscosity final polycondensation reaction. The reaction lasts for 1 hour. The material is discharged, granulated and cooled to obtain thermoplastic polyether ester elastomer. The thermoplastic polyether ester elastomer is extruded and spun to obtain a 3D fiber network hollow structure.

[0103] Comparative Example 3

[0104] This comparative example provides a 3D fiber mesh hollow structure, the preparation method of which includes the following steps:

[0105] S1. 70 parts of diphenyl phthalate, 15 parts of diethylene glycol diethyl ether, 0.2 parts of zirconium tetroxide and 10 parts of EVA-g-MAH / high melt index low melting point grafted polymer TPU (the weight ratio between EVA-g-MAH and high melt index low melting point grafted polymer TPU is 1 to 1) were placed in a nitrogen-filled polymerization reactor and reacted at 160°C for 50 min to obtain transesterification and grafting products.

[0106] S2. Add 0.2 parts of carboxyl water-soluble ZnCdSe / ZnS quantum dots to 15 parts of diethylene glycol diethyl ether solvent and sonicate for 1 hour under constant temperature and constant speed stirring at 60℃ to obtain a homogeneous diethylene glycol diethyl ether mixture.

[0107] S3. When the amount of alcohol in the transesterification and grafting product obtained in step S1 reaches more than 120% of the amount of diphenyl phthalate, add the diethylene glycol diethyl ether mixture obtained in step S2 to the polymerization reactor in step S1, and add 0.2 parts of aluminum distearate at the same time to carry out a second reaction for 0.5 hours.

[0108] S4. When the viscosity of the mixture in the polymerization reactor in step S3 reaches 6000 Pa·s, the nitrogen gas in the reactor is removed to a vacuum negative pressure of 0.1 MPa. At the same time, the temperature is raised to 240℃ to carry out a low-viscosity final polycondensation reaction in a vacuum for 1.5 hours. The material is discharged, granulated, and cooled to obtain thermoplastic polyether ester elastomer. The thermoplastic polyether ester elastomer can be extruded and spun to obtain a 3D fiber network hollow structure.

[0109] Comparative Example 4

[0110] This comparative example provides a 3D fiber mesh hollow structure, the preparation method of which includes the following steps:

[0111] S1. Place 60 parts of butylene 2,6-naphthalenedioate, 20 parts of polytetrahydrofuran ether diol, 0.05 parts of organotitanium zirconium chelate and 3 parts of EMA-g-GMA in a nitrogen-filled polymerization reactor and react at 210°C for 120 min to obtain transesterification and grafting products.

[0112] S2. The dried tungsten disulfide nanotubes without hydroxyl or carboxyl groups were immersed in an acid solution (a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1) and oxidized at 100°C for 8 hours. After cleaning with ethanol and drying, tungsten disulfide nanotubes modified with hydroxyl and carboxyl groups were obtained.

[0113] S3. Add 0.5 parts of hydroxyl and carboxyl-modified transition metal tungsten disulfide nanotubes to 20 parts of polytetrahydrofuran ether diol solvent, and then sonicate for 2 hours under constant temperature and constant speed stirring at 60℃ to obtain a homogeneous polytetrahydrofuran ether diol mixture.

[0114] S4. When the amount of alcohol in the transesterification and grafting product obtained in step S1 reaches more than 120% of the amount of butylene 2,6-naphthalenedioate, add the polytetrahydrofuran ether diol mixture obtained in step S3 to the polymerization reactor in step S1, and add 0.5 parts of citrate monostearate at the same time to carry out a secondary reaction, which lasts for 0.5 hours.

[0115] S5. When the viscosity of the mixture in the polymerization reactor in step S4 reaches 5000 Pa·s, the nitrogen gas in the polymerization reactor is removed to a vacuum negative pressure of 0.4 MPa. At the same time, the temperature is raised to 200℃ to carry out a low-viscosity final polycondensation reaction in a vacuum for 1 hour. The material is discharged, granulated, and cooled to obtain thermoplastic polyether ester elastomer. The thermoplastic polyether ester elastomer can be extruded and spun to obtain a 3D fiber network hollow structure.

[0116] Comparative Example 5

[0117] Comparative Example 1 provides a 3D fiber mesh hollow structure, the preparation method of which includes the following steps:

[0118] S1. Place 60 parts of butylene 2,6-naphthalenedioate, 20 parts of polytetrahydrofuran ether diol, 0.05 parts of organotitanium zirconium chelate and 3 parts of EMA-g-GMA in a nitrogen-filled polymerization reactor and react at 210°C for 120 min to obtain transesterification and grafting products.

[0119] S2. The dried graphene / platinum diselenide (PtSe2) van der Waals heterostructure without hydroxyl or carboxyl groups was immersed in an acid solution (a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1) and oxidized at 120°C for 8 hours. Then, it was cleaned with ethanol and dried to obtain graphene / platinum diselenide (PtSe2) van der Waals heterostructure modified with hydroxyl and carboxyl groups.

[0120] S3. Add 1 part of graphene / platinum diselenide (PtSe2) van der Waals heterostructure modified with hydroxyl and carboxyl groups to 20 parts of polytetrahydrofuran ether diol solvent, and then sonicate at 60°C with constant temperature and speed stirring for 2 hours to obtain a homogeneous polytetrahydrofuran ether diol mixture.

[0121] S4. When the amount of alcohol in the transesterification and grafting product obtained in step S1 reaches more than 120% of the amount of butylene 2,6-naphthalenedioate, add the polytetrahydrofuran ether diol mixture obtained in step S3 to the polymerization reactor in step S1, and add 0.5 parts of citrate monostearate at the same time to carry out a secondary reaction, which lasts for 0.5 hours.

[0122] S5. When the viscosity of the mixture in the polymerization reactor in step S4 reaches 5000 Pa·s, the nitrogen gas in the polymerization reactor is removed to a vacuum negative pressure of 0.4 MPa. At the same time, the temperature is raised to 200℃ to carry out a low-viscosity final polycondensation reaction in a vacuum for 1 hour. The material is discharged, granulated, and cooled to obtain thermoplastic polyether ester elastomer. The thermoplastic polyether ester elastomer can be extruded and spun to obtain a 3D fiber network hollow structure.

[0123] Comparative Example 6

[0124] Comparative Example 1 provides a 3D fiber mesh hollow structure, the preparation method of which includes the following steps:

[0125] S1. Place 60 parts of butylene 2,6-naphthalenedioate, 20 parts of polytetrahydrofuran ether diol, 0.05 parts of organotitanium zirconium chelate and 3 parts of EMA-g-GMA in a nitrogen-filled polymerization reactor and react at 160°C for 50 min to obtain transesterification and grafting products.

[0126] S2. When the amount of alcohol in the transesterification and grafting product obtained in step S1 reaches more than 120% of the amount of butylene 2,6-naphthalenedioate, the polymerization kettle is heated to 200°C, and 0.5 parts of monostearate citrate are added at the same time to carry out a second reaction for 0.5 hours.

[0127] S3. When the viscosity of the mixture in the polymerization reactor in step S2 reaches 4000 Pa·s, the nitrogen in the polymerization reactor is removed to a vacuum negative pressure of 0.03 MPa, and the temperature is raised to 240℃ to carry out a final viscosity condensation reaction in a vacuum for 2 hours. The material is discharged, granulated, and cooled to obtain thermoplastic polyether ester elastomer.

[0128] S4. The dried graphene quantum dots, tungsten disulfide nanotubes, and graphene / platinum diselenide (PtSe2) van der Waals heterostructures without hydroxyl or carboxyl groups were each immersed in an acid solution (a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1) and oxidized at constant temperatures of 80℃, 100℃, and 120℃ for 8 hours, respectively. After cleaning with ethanol and drying, hydroxyl and carboxyl modified graphene quantum dots, tungsten disulfide nanotubes, and graphene / platinum diselenide (PtSe2) van der Waals heterostructures were obtained.

[0129] S5. The thermoplastic polyether ester elastomer obtained in step S4 is fed together with 0.5 parts of hydroxyl and carboxyl-modified graphene quantum dots, 0.5 parts of hydroxyl and carboxyl-modified transition metal tungsten disulfide nanotubes, and 1 part of hydroxyl and carboxyl-modified graphene / platinum diselenide (PtSe2) van der Waals heterostructure into a twin-screw extruder with an aspect ratio of 56 for melt blending and extrusion granulation. The resulting granules are then extruded and spun to obtain a 3D fibrous network hollow structure.

[0130] The amounts of each raw material used in Examples 1-4 are shown in Table 1, and the amounts of each raw material used in Comparative Examples 1-6 are shown in Table 2.

[0131] Table 1 Raw material usage in Examples 1-4

[0132]

[0133]

[0134] Table 2 Raw material usage for Comparative Examples 1-6

[0135]

[0136]

[0137] Test case

[0138] The polyether ester thermoplastic elastomers and 3D fiber mesh hollow structures prepared in Examples 1-4 and Comparative Examples 1-6 were tested separately, and the performance parameters are shown in Table 3.

[0139] The performance testing standards for the polyether ester thermoplastic elastomers and 3D fiber mesh hollow structures prepared in Examples 1-4 and Comparative Examples 1-6 are as follows:

[0140] Melting point (Tm) and glass transition temperature (Tg): GB / T 19466.3-2004; Melt mass flow rate (MFR) of materials: GB / T 3682.1-2018; High and low temperature creep resistance: Refer to the compressive residual strain measurement method disclosed in patent publication number CN105683434A.

[0141] A simplified method for manufacturing hollow parts of a melt-extruded coarse and long fiber structure: The polyether ester thermoplastic elastomer prepared in this invention is extruded through a melt-spinning sprayer (φ0.3mm×10000 holes) at a constant pressure and constant rate under a constant temperature (240℃). It falls directly into a circulating water tank (the distance between the water surface and the melt-spinning sprayer is 1-10cm) for cooling. The continuous lines are bent into rings, and the contact parts are fused together. Then, both sides are flattened, and finally, it is cut into the required size to obtain a fiber block with a three-dimensional network structure.

[0142] Residual strain was used to characterize the creep and shape retention rate of the finished 3D fiber hollow mesh structure. The test method, referring to patent publication number CN105683434A, involved placing a cut fiber block (30cm×30cm×10cm) under alternating temperature conditions of -40 to 70℃ and compressing it at a constant stress of 40 kgf at 50% for 1008 hours. Immediately afterward, the block was placed in constant temperature and humidity environments at room temperature and 80℃. Residual strain was measured every 10 minutes. A shorter shape recovery time and smaller residual strain indicate better high and low temperature creep resistance and thermal deformation memory recovery characteristics of the finished 3D fiber hollow mesh structure.

[0143] Support factor test: At a constant temperature of 23℃, the prepared fiber block was placed between two pressure plates. At a test speed of 100mm / min, the upper pressure plate was lowered to compress the fiber block, reducing the strain to 65% and 25% of the original fiber block thickness. The pressure readings of the upper pressure plate were recorded as F65% and F25%, respectively. The support factor Sf = F65% / F25%. Each sample was tested five times throughout the process, and the average support factor was calculated. A higher support factor indicates better product comfort and support.

[0144] Table 3 shows the performance test results of the polyether ester thermoplastic elastomers and finished products prepared in each example and comparative example.

[0145]

[0146]

[0147] The data in Table 3 shows that:

[0148] 1. The polyether ester thermoplastic elastomers prepared in Examples 1-4 and Comparative Examples 1-3 have melting points below 230℃-250℃ and melt index between 20 and 50 g / 10min (230℃, 2.16 kg), which is within a moderate range and meets the requirements for underwater melt bonding and welding processing. Therefore, they can all be spun into fiber structures.

[0149] 2. Compared with Comparative Example 1 (without the introduction of low-melting-point grafted polymers, zero-dimensional carbon materials, carboxyl rod-shaped materials, and van der Waals heterostructures), the polyether ester thermoplastic elastomer prepared in Example 1 still maintains the higher MFR value of Comparative Example 1. The melting point, glass transition temperature, and compression set at -40~70℃ / 1008h are significantly reduced, while the fiber bonding density of the finished 3D air fiber hollow structure increases to 832 fibers / m. 2 Furthermore, the support factor increased to 4.9, indicating that the polyether ester thermoplastic elastomer prepared in Example 1 not only has good underwater adhesion performance, but also the 3D fiber hollow structure obtained by molding exhibits good high and low temperature creep resistance, as well as high support force and comfort, while possessing electro-thermal induced shape memory rapid rebound response characteristics.

[0150] 3. Compared with Comparative Example 2 (which only did not introduce low-melting-point grafted polymer), the melting point and glass transition temperature of the polyether ester thermoplastic elastomer prepared in Example 2 were significantly reduced, the MFR was significantly increased, and the fiber bonding density and support factor of the finished product were greatly improved, while the compression set was significantly reduced. This indicates that the low-melting-point grafted polymer can improve the flowability and underwater bonding density of polyether ester thermoplastic elastomer, indirectly reducing the compression set of the finished 3D air fiber hollow structure and improving the support and comfort of the finished product.

[0151] 4. Compared with Comparative Example 3 (which only introduced low-melting-point grafted polymers and zero-dimensional carbon materials), the polyether ester thermoplastic elastomer prepared in Example 3 can be spun into fibrous structures, mainly because the composition has a sufficiently large MFR and flows quickly.

[0152] 5. Compared to Comparative Example 4 (which only introduced a low-melting-point grafted polymer and carboxyl rod material), the polyether ester thermoplastic elastomer composition prepared in Experimental Example 4 showed improved melting point, crystallization temperature, MFR, elongation at break, and support factor, while reducing compression set. Similarly, compared to Comparative Example 5 (which only introduced a low-melting-point grafted polymer and van der Waals heterostructure) and Comparative Example 6 (which used a reactive extrusion melt blending process), the polyether ester thermoplastic elastomer composition prepared in Experimental Example 4 showed similar results. In summary, the polyether ester thermoplastic elastomer composition prepared in Experimental Example 4 exhibited the highest melting point, crystallization temperature, elongation at break, and support factor, while showing the lowest compression set, indicating that the polyether ester thermoplastic elastomer composition prepared in Experimental Example 4 possessed a higher support factor and better comfort than the comparative examples above.

[0153] In summary, the polyether ester thermoplastic elastomer composition with low melting point, glass transition temperature, and high MFR involved in this invention, when processed into spun fiber structures, exhibits good resilience and comfort. Furthermore, the combined effects of low-melting-point grafted polymers, zero-dimensional carbon materials, carboxyl / hydroxyl rod-shaped materials, and van der Waals heterostructures can yield ideal spun fiber structures with high adhesion, creep resistance, and a certain shape memory resilience response. In particular, the high-hardness resin preparation, while retaining the original good support effect, possesses excellent resilience and comfort.

[0154] Industrial applicability: The 3D fiber mesh hollow structure involved in this invention can be used in ergonomic seat cushion cores, mattress cores, backrest cushion cores, etc. It has good load-bearing support and comfort for sitting or lying down. It does not have the defects of poor ventilation, stuffiness and creep caused by long-term use of polyurethane foam. It can maintain the low deformation and shape of the 3D fiber mesh hollow structure after long-term repeated compression. It is suitable for heated chairs, sofas, beds and other household / public furniture, heated seats and backrests of vehicles such as cars, high-speed trains, airplanes and ships, and cold-proof and warm cushioning pads for nursery floors, etc.

[0155] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0156] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A 3D fiber mesh hollow structure with high adhesion, high support, and resistance to high and low temperature creep, characterized in that, It is prepared from the following components in parts by weight: 35-90 parts benzoate and its derivatives, 10-65 parts polyether alcohol, 0.05-0.2 parts catalyst, 2-20 parts low melting point graft polymer, 0-2 parts hydroxyl and / or carboxyl modified zero-dimensional carbon material, 0.2-2 parts hydroxyl and / or carboxyl modified needle or rod material, 0.2-2 parts hydroxyl and / or carboxyl modified van der Waals heterostructure, and 0.2-2 parts processing aid; Zero-dimensional carbon materials have a non-zero weight component; The preparation method of the high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber mesh hollow structure includes the following steps: S1. Add benzoic acid esters and their derivatives, catalysts and low-melting-point grafted polymers to a nitrogen-filled polymerization reactor in proportion, and add polyether alcohol accounting for 40-80% of the total amount of polyether alcohol. React at 160-240ºC for 40-120 min to obtain transesterification and grafting products. S2. Hydroxyl and / or carboxyl groups are used to modify zero-dimensional carbon materials, needle-shaped or rod-shaped materials, and van der Waals heterostructures to obtain zero-dimensional carbon materials, needle-shaped or rod-shaped materials, and van der Waals heterostructures modified with hydroxyl and / or carboxyl groups. S3. Under constant temperature conditions of 60-100ºC, the zero-dimensional carbon material modified with hydroxyl and / or carboxyl groups is added to the remaining polyether alcohol in proportion and ultrasonically stirred. Then, the needle or rod-shaped material modified with hydroxyl and / or carboxyl groups is added in proportion and ultrasonically stirred again. Finally, the van der Waals heterostructure modified with hydroxyl and / or carboxyl groups is added in proportion and ultrasonically stirred again to obtain a homogeneous polyether alcohol mixture. S4. Add the polyether alcohol mixture to the polymerization reactor, and add processing aids in proportion, and carry out a secondary reaction with the transesterification and grafting product for 0.5 to 2 hours. S5. Remove nitrogen from the polymerization reactor to a vacuum negative pressure of 0.02-0.4 MPa, and simultaneously raise the temperature to 190-230ºC to carry out a vacuum low-viscosity final polycondensation reaction for 1-2 hours. Discharge and granulate to obtain thermoplastic polyether ester elastomer. Extrude and spin the thermoplastic polyether ester elastomer to obtain a high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber network hollow structure.

2. The high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber mesh hollow structure according to claim 1, characterized in that, The zero-dimensional carbon material is at least one of the following: carboxyl / amino modified carbon quantum dots, carbon quantum dot modified polyethylene glycol adamantane, carboxyl water-soluble ZnCdSe / ZnS quantum dots, copper carbon quantum dots, perovskite quantum dots, cyclodextrin modified calcium phosphate nanoparticles / zinc sulfide quantum dots, cadmium selenide quantum dots, indium phosphide quantum dots, graphene quantum dots, graphitic carbon nitride quantum dots, PEG-functionalized graphene quantum dots loaded with cisplatin, gold nanoparticles, and silver nanoparticles.

3. The high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber mesh hollow structure according to claim 1, characterized in that, The needle or rod-shaped material is at least one of titanium dioxide nanofibers, carboxyl carbon nanotubes, carbon nanofibers, and transition metal dichalcogenide nanotubes. And / or, the aspect ratio of the needle or rod material is 1.5:1 to 5:

1.

4. The high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber mesh hollow structure according to claim 1, characterized in that, The van der Waals heterostructures are: graphene / graphene stacked van der Waals heterostructures, graphene / molybdenum disulfide van der Waals heterostructures, graphene / gallium phosphide van der Waals heterostructures, graphene / boron boron nitride van der Waals heterostructures, graphene / hexagonal boron nitride / molybdenum disulfide van der Waals heterostructures, molybdenum disulfide / antimony trisulfide van der Waals heterostructures, black phosphorus / molybdenum disulfide van der Waals heterostructures, graphene / trinitrobenzene van der Waals heterostructures, graphene / titanium dioxide van der Waals heterostructures, and graphene / ... The following are at least one of the following: metal dihalide MX2 van der Waals heterostructure, molybdenum disulfide / titanium trisulfide van der Waals heterostructure, graphene / nano-silica van der Waals heterostructure, black phosphorus / germanium phosphide van der Waals heterostructure, molybdenum disulfide / gallium phosphide van der Waals heterostructure, graphene / copper selenide van der Waals heterostructure, graphene / gallium nitride van der Waals heterostructure, black phosphorus / antimony trisulfide van der Waals heterostructure, indium tin oxide / aluminum oxide van der Waals heterostructure, and graphene / silica nanowire van der Waals heterostructure.

5. The high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber mesh hollow structure according to claim 1, characterized in that, The benzoic acid esters and their derivatives are at least one of dimethyl phthalate, dimethyl isophthalate, ethylene isophthalate, ethylene phthalate, propylene isophthalate, butylene isophthalate, butylene phthalate, diphenyl phthalate, a copolymer of dimethyl 1,4-phthalate with 1,4-cyclohexanediol and 1,2-ethylene glycol, 1,4-dimethylenecyclohexane terephthalate, and butylene 2,6-naphthalenedicarboxylate.

6. The high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber mesh hollow structure according to claim 1, characterized in that, The polyether alcohol is at least one of polyoxypropylene polyol, diethylene glycol diethyl ether, polyoxytetramethylene polyol, and tetrahydrofuran-propylene oxide copolydiol.

7. The high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber mesh hollow structure according to claim 1, characterized in that, The low-melting-point graft polymer is an AgB-type graft polymer or a high melt index, low-melting-point hot-melt polyurethane.

8. The high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber mesh hollow structure according to claim 1, characterized in that, The catalyst is one of zirconium oxide, zirconium hydroxide, and ruthenium / zirconium chelate; And / or, the processing aid is at least one of the following: long-chain linear saturated lignite, sodium dodecyl sulfate, sodium allyl sulfonate, potassium dodecylbenzene sulfonate, calcium stearate, aluminum stearate, calcium distearate, aluminum distearate, aluminum dihydroxystearate, glyceryl monostearate, stearyl citrate, and quaternary ammonium salt.

9. The high-adhesion, high-support, high- and low-temperature creep-resistant 3D fiber mesh hollow structure according to claim 1, characterized in that, In step S2, the hydroxyl and / or carboxyl modification process is as follows: the zero-dimensional carbon material, needle or rod-shaped material, and van der Waals heterostructure are respectively immersed in an acid solution and oxidized at a constant temperature of 80-120ºC for 8 hours; then washed and dried to obtain zero-dimensional carbon material, needle or rod-shaped material, and van der Waals heterostructure modified with hydroxyl and / or carboxyl groups; the acid solution is a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:

1. And / or, in step S4, when the amount of alcohol in the transesterification and grafting product reaches more than 120% of the amount of benzoate and its derivatives, the polyether alcohol mixture is added. And / or, in step S5, when the viscosity of the mixture in the polymerization reactor reaches 4000-6000 Pa•s, the nitrogen in the polymerization reactor is then purged to a vacuum negative pressure of 0.02-0.4 MPa.

Citation Information

Patent Citations

  • Network structure having excellent durability against compression

    CN105683434A

  • Method for preparing 2-methyl-1, 3-propanediol ester polyterephthalate and copolyester elastomer thereof

    CN102093545A

  • Quantum titanium fiber material

    CN110016731A